FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI SAWAH LEBAK DI KABUPATEN OGAN ILIR - Sari, Komala (AGRIPITA JOURNAL, 2018)
Maju Jaya village is located in Ogan Ilir South Sumatra which is the central lowland rice production. This study aims to determine farmer revenue and factors that affect farmers' income of lowland rice in the Ogan Ilir District. Samples farmer choose for this study are 30 out of 187 farmers who cultivate paddy in Maju Jaya Village. Data processing was done by using income analysis and multiple linear regression analysis, followed by statistical ftest and t-test statistic. The results of this study addressing the average lowland rice production in Maju Jaya Village was 3532.31 kg / season / ha with an average income of IDR 11,600,803.40 /ha /season. The analysis results showed that the revenue function of the factors that significantly affect revenue of lowland rice farmer are the experience, the production and selling prices of grain and land size. Factors which are not significantly affect the income of farmers of lowland rice is technology.